CHALLENGES FACED BY TOUR GUIDES IN THE MODERN TOURISM INDUSTRY - Ro`ziboyeva Dilnura Abduvohid qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: In the rapidly transforming landscape of global tourism, tour guides remain central to shaping travelers’ experiences, providing information, facilitating interaction with local communities, and ensuring the overall satisfaction and safety of tourists. They serve not only as narrators of history and culture but also as cultural ambassadors, logistics coordinators, conflict managers, and sometimes even caretakers. However, as the global tourism industry expands and evolves in the 21st century, tour guides are facing a growing number of complex and interrelated challenges. These difficulties stem from technological disruption, shifting consumer preferences, environmental and cultural pressures, economic vulnerabilities, and systemic undervaluation of the profession. This article explores these challenges in depth and provides a nuanced understanding of how they impact the profession and the broader tourism ecosystem.